Farmers' Perception about Climate Change and Response Strategies - Bharat,; Chapke, R.R.; Kammar, Shivanand (Indian Journal of Extension Education, 2021)
The crop production response strategies to climate change and variability vis-Ã -vis their socio-personal characterstics in North-Eastern Karnataka region were identified and analysed. A multi-stage random sampling technique was employed to elicit information from 120 respondents.. Ex-post-facto research design was adopted as manifestation of event was already accured. Data were collected through a pre-tested semi-structured questionnaire Total 52 strategies were colleted from different literature, website, thesis etc., and tested among the respondents. The study revealed that there were eight commonly adopted crop production response strategies which were scrutinsed from the 30 selected strategies using principal coponent analysis namely, soil-water retention and integrated farming, followed by, contingency crop planning, crop diversification and risk aversion strategies, seeking advice from extension personnel and others, improving irrigation facilities, maintaining livestock, crop insurance, and migration to cities. The farmersâ€™ education, mass media use and source of weather information were significantly contributed in their perception about climate change and varibility at 5% level of probability.